1976
DOI: 10.1172/jci108416
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of 3-hydroxy-3-methylglutaryl coenzyme A reductase in the isolated perfused rat liver.

Abstract: A B S T R A C T The effect of perfusion of an isolated rat liver on hepatic 3-hydroxy-3-methylglutaryl coenzyme A reductase was studied. In liver removed during the basal period of the diurnal cycle of enzyme activity, a 227±41% increase in enzyme activity occurred after 3 h of a l)lasna-free perfusion. This could be prevented by the addition of cycloheximide or pure cholesterol (dispersed with lecithin) to the perfusate. In contrast, the continuous addition of taurocholate or taurochenodeoxycholate, alone or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 47 publications
3
9
0
Order By: Relevance
“…6, a twofold increase in the activity of the enzyme was noted at the end of the perfusion period in livers, which had been perfused in the absence of lipoproteins in the medium. This may be due to the loss of cholesterol by the liver during perfusion (38). Addition of LDL to the medium did not suppress this increase in enzyme activity.…”
Section: Removal Oflp-x In Vivomentioning
confidence: 82%
“…6, a twofold increase in the activity of the enzyme was noted at the end of the perfusion period in livers, which had been perfused in the absence of lipoproteins in the medium. This may be due to the loss of cholesterol by the liver during perfusion (38). Addition of LDL to the medium did not suppress this increase in enzyme activity.…”
Section: Removal Oflp-x In Vivomentioning
confidence: 82%
“…However, a thorough series of studies by Turley and Dietschy (6) in the rat suggested that the rate of hepatic cholesterol synthesis per se does not determine the rate of biliary cholesterol secretion. Moreover, it has been shown that chenodeoxycholate's mechanism of action is not through direct inhibition of HMG CoA reductase (15). Lastly, under normal circumstances, only 10-20% ofbiliary cholesterol is derived from new synthesis (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…First, experiments performed in vitro [7,8] and in thc perfused liver [24,25] gave no evidence of a rapid inhibition of cholesterogenic enzymes by bile salts. Moreover, wc observed a coincidence of a greater sensitivity of inhibition by bile salts apparent at 22 h with the diurnal phase of most active synthesis of the 3-hydroxy-3-methylglutarylCoA reductase protein [26].…”
Section: Discuss I 0 Nmentioning
confidence: 99%
“…Although our results do not allow final conclusions as to the mechanisms mediating the inhibition it is tempting to speculate that it is caused by inhibition of enzyme synthesis rather than by inhibition ofpreexist-ing enzyme molecules. First, experiments performed in vitro [7,8] and in thc perfused liver [24,25] gave no evidence of a rapid inhibition of cholesterogenic enzymes by bile salts. Moreover, wc observed a coincidence of a greater sensitivity of inhibition by bile salts apparent at 22 h with the diurnal phase of most active synthesis of the 3-hydroxy-3-methylglutaryl-CoA reductase protein [26].…”
Section: Discuss I 0 Nmentioning
confidence: 99%